Peningkatan Produksi Ikan Lele Desa Gedong Kecamatan Banyubiru - Yunus, Mahmud (Journal of Dedicators Community, 2022)
One of the catfish breeding areas in Semarang Regency, Central Java is Gedong Village, Banyubiru District. The population in Gedong Village is sufficient large also affects the fulfillment of large needs, especially in terms of fulfillment of large food needs. Based on the results of observations, some people Gedong Village has a job as a catfish farmer. In catfish nurseries The people of Gedong Village still use the natural spawning system. However the system is less suitablebecause of the process that takes a long time and results from the spawning is not maximal. Based on this background, the KKN Team PGRI University in Semarang has a solution to solve problems in the village Gedong, Banyubiru District, Semarang Regency by conducting training artificial insemination to increase production of quality catfish in quantity time-effective. Besides that, it also conducts catfish processing training and provides online marketing training